Introductory transport phenomena - Bird, Robert Byron 1924-2020; Stewart, Warren E. 1924-; Lightfoot, Edwin N. 1925-; Klingenberg, Daniel J. (Wiley, 2015)
"The first seven chapters of this book deal with the flow of viscous fluids of molecular weight less than about 1000 g/g-mol, such as air, water, benzene, and glycerin"...